Delayed Bleeding Following Cold Snare Polypectomy for Small Colorectal Polyps in Patients Taking Antithrombotic Agents. Issue 6 (July 2018) - Makino, Toshiyuki; Horiuchi, Akira; Kajiyama, Masashi; Tanaka, Naoki; Sano, Kenji; Maetani, Iruru
Abstract : Background: This study compared the incidence of delayed bleeding following 2 methods of cold snare polypectomy for colorectal polyps in patients taking antithrombotic agents. Methods: Patients undergoing cold snare polypectomy for colorectal polyps ⩽10 mm without discontinuation of antithrombotic agents were enrolled. This was a retrospective study of a prospectively collected cohort based on a historical comparison of 2 time periods. A traditional cold snare was used between January 2012 and December 2013 and a dedicated cold snare was used between January 2014 and December 2015. Patients' and polyps' characteristics, antithrombotic agents used, the snare used, the number of clips used, and adverse events were documented from a hospital online database. Delayed bleeding was defined as bleeding that required endoscopic treatment within 2 weeks after polypectomy. The submucosal layer of the resected polyps (6 to 10 mm) was histologically examined for the presence of injured arteries. Results: A total of 172 patients having 370 eligible polyps were enrolled; traditional cold snare group, N=100 (212 polyps) and dedicated cold snare group, N=72 (158 polyps). The patients' and polyps' characteristics were similar between the 2 groups. Hemostatic clips were used more often with the traditional than dedicated cold snares [33/100 (33%) vs. 13/72 (18%), P =0.044]. Delayed bleeding following cold snare polypectomy occurred in 1.2% (2/172); 0% (0/72) with dedicated snare versus 2% (2/100) with the traditional snare ( P =0.63). The presence of histologically demonstrated injured submucosal arteries with the dedicated cold snare was significantly less than with the traditional cold snare [4.1% (4/98) vs. 16% (17/105), P =0.009]. Conclusions: Colorectal polyps ⩽10 mm can be removed without an increase in delayed bleeding using dedicated cold snare polypectomy in patients taking antithrombotic agents.